Investigating the motivation for enterprise education: a CaRBS based exposition. Issue 6 (26th August 2014) - J. Beynon, Malcolm; Jones, Paul; Packham, Gary; Pickernell, David
Abstract : Purpose: – The purpose of this paper is to investigate student motivation for undertaking an entrepreneurship education programme and their ultimate employment aspirations through a novel data mining technique. The study considered what relationship certain motivation characteristics have to students' aspirations, specifically in terms of their intention to be self-employed or employed. Design/methodology/approach: – The study examined enrolment data of 720 students on an entrepreneurial education programme, with work statuses of full-time, part-time or unemployed and have known aspirations to either employment or self-employment. The Classification and Ranking Belief Simplex (CaRBS) technique is employed in the classification analyses undertaken, which offers an uncertain reasoning based visual approach to the exposition of findings. Findings: – The classification findings demonstrate the level of contribution of the different motivations to the discernment of students with self-employed and employed aspirations. The most contributing aspirations were Start-Up, Interests and Qualifications. For these aspirations, further understanding is provided with respect to gender and student age (in terms of the association with aspirations towards self-employed or employed). For example, with respect to Start-Up, the older the unemployed student, the increasing association with employment rather than self-employment career aspirations. Research limitations/implications: – The study identifies candidate motivation and the demographic profile for student's undertaking an entrepreneurial education programme. Knowing applicant aspirations should inform course design, pedagogy and its inherent flexibility and recognise the specific needs of certain student groups. Originality/value: – The study contributes to the literature examining motivations for undertaking entrepreneurship education and categorising motivating factors. These findings will be of value to both education providers and researchers.